Implementation of Discovery Learning Model in Improving Motivation and Learning Outcomes of Civic Education: Penerapan Model Pembelajaran Discovery Learning dalam Meningkatkan Motivasi dan Hasil Belajar Pendidikan Kewarganegaraan - Nurmala, Eka; Sultan; Baihaqi; Kurnia, Rahmat; Fauzi, Chairul (PT. Alpha Trianguli Australis, 2024)
Many of the students in various educational institutions in the shipping sector consider the subject of civic education to be a less interesting subject to follow so it affects the motivation and learning outcomes of civic education itself. This research is important to be carried out to improve the quality of civic education learning by applying the discovery learning model by inviting students to understand concepts, meanings, and relationships through an intuitive process to conclude finally. This research is also a classroom action research that uses a qualitative approach with a descriptive analysis method. The results of this study are expected to be useful for educators in educational institutions in the shipping sector in applying a new model to be able to increase motivation and learning outcomes.